Biogenic Synthesis of Silver Nanoparticles (AgNPs) Using Aqueous Leaf Extract of Buchanania lanzan Spreng and Evaluation of Their Antifungal Activity against Phytopathogenic Fungi. (10th March 2022) - Purohit, Ayushi; Sharma, Radheshyam; Shiv Ramakrishnan, R.; Sharma, Stuti; Kumar, Ashish; Jain, Devendra; Kushwaha, Himmat S.; Maharjan, Elina
Abstract : Nanoparticles show the multidisciplinary versatile utility and are gaining the prime place in various fields, such as medicine, electronics, pharmaceuticals, electrical designing, cosmetics, food industries, and agriculture, due to their small size and large surface to volume ratio. Biogenic or green synthesis methods are environmentally friendly, economically feasible, rapid, free of organic solvents, and reliable over conventional methods. Plant extracts are of incredible potential in the biosynthesis of metal nanoparticles owing to their bountiful availability, stabilizing, and reducing ability. In the present study, the aqueous leaf extract of Buchanania lanzan Spreng was mixed with 0.5 mM silver nitrate and incubated at 70°C for 1 h and synthesized a good quantity of AgNPs. The synthesized AgNPs were characterized using UV-visible spectroscopy, X-ray diffractometry (XRD), dynamic light scattering (DLS), transmission electron microscopy (TEM), and scanning electron microscopy (SEM). The maximum absorption of UV-visible spectra was obtained in the range of 420–430 nm. Furthermore, SEM and TEM results inferred that the size of the particles were 23–62 nm, spherical, crystalline, uniformly distributed, and negatively charged with the zeta potential of −27.6 mV. In addition, the antifungal activities of the AgNPs were evaluated against two phytopathogenic fungi Rhizoctonia solani and Fusarium oxysporum f. sp. lycopersici in vitro using poison food techniques on PDA media. The maximum rate of mycelia inhibition was found in 150 ppm concentration of AgNPs against both phytopathogenic fungi.